2020
DOI: 10.7717/peerj.9625
|View full text |Cite
|
Sign up to set email alerts
|

Classification of genomic components and prediction of genes of Begomovirus based on subsequence natural vector and support vector machine

Abstract: Background Begomoviruses are widely distributed and causing devastating diseases in many crops. According to the number of genomic components, a begomovirus is known as either monopartite or bipartite begomovirus. Both the monopartite and bipartite begomoviruses have the DNA-A component which encodes all essential proteins for virus functions, while the bipartite begomoviruses still contain the DNA-B component. The satellite molecules, known as betasatellites, alphasatellites or deltasatellites,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Taken together, it suggested that the MCRSVMC algorithm was highly efficient and stable. e activated brain areas in the healthy control group during the verb association task mainly included auxiliary motor area, right Broca area, right anterior cingulate gyrus, and left fusiform gyrus, indicating that the verb association task mainly activated the frontal parietal cortex, and the bilateral occipital area was activated by a small area [21][22][23]. e Scientific Programming activated brain areas for picture naming mainly included the right visual cortex, left fusiform gyrus, and left Broca, indicating that the picture naming mainly activated bilateral occipital lobes in the visual cortex, which was consistent with the results of Tan et al [24].…”
Section: Discussionmentioning
confidence: 98%
“…Taken together, it suggested that the MCRSVMC algorithm was highly efficient and stable. e activated brain areas in the healthy control group during the verb association task mainly included auxiliary motor area, right Broca area, right anterior cingulate gyrus, and left fusiform gyrus, indicating that the verb association task mainly activated the frontal parietal cortex, and the bilateral occipital area was activated by a small area [21][22][23]. e Scientific Programming activated brain areas for picture naming mainly included the right visual cortex, left fusiform gyrus, and left Broca, indicating that the picture naming mainly activated bilateral occipital lobes in the visual cortex, which was consistent with the results of Tan et al [24].…”
Section: Discussionmentioning
confidence: 98%
“…The biological similarity between two sequences can be measured using the Euclidean distance of their corresponding 18-dimensional natural vectors, which is commonly used in our previous studies ( Deng et al, 2011 ; Zhao, Tian & Yau, 2018 ; Zhao et al, 2019 ; Sun et al, 2021 ; He et al, 2020 ; Pei et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…This natural vector consists of the count, average position and central moment of each nucleotide. It has been successfully applied to many research fields, especially the clustering ( Zhao, Tian & Yau, 2018 ; Zhao et al, 2019 ; Sun et al, 2021 ) and classification ( He et al, 2020 ; Pei et al, 2020 ) of biological sequences. The 12-dimensional natural vector only considers the respective distribution of single nucleotide but ignores the relationship between the two nucleotides.…”
Section: Introductionmentioning
confidence: 99%